Visualizing real-world relational database schema - Chua, Ming Kiang (Nanyang Technological University, 2023)
Relational databases are important in data storage, management, and retrieval. Understanding the schema is paramount to effectively leverage such databases, especially in formulating optimized Structured Query Language (SQL) queries. However, as data grows in this digital age, real-world databases are expanding correspondingly to keep up, often encompassing dozens to hundreds of relations, each potentially having hundreds of attributes. Such complexity poses a significant challenge for users to navigate the database schema effectively to pose queries. This research delves into potential methods to enhance visualization techniques. It focuses on balancing better visual representation, features, and information to provide a holistic yet clear view of the database schema.